Perspectives on Postal Service issues : a conference sponsored by the American Enterprise Institute for Public Policy Research - Sherman, Roger; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
This 1980 volume assesses postal reorganization since 1970. It also describes future technical opportunities and the expected economic, legal, and political responses.
Includes bibliographical footnotes.
II 16/01/2019
Loans
Keywords: Postal service